Hubungan Paparan Rokok dan Alkohol dengan Kejadian Abortus pada Ibu Hamil di Desa - Ula, Zumrotul; Hamzah, Abd Natsir (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Abortion is a reproductive health issue with a high prevalence in Indonesia. Several risk factors contribute to the incidence of abortion, including exposure to harmful substances such as cigarettes and alcohol. Village X is an area with a high prevalence of cigarette and alcohol consumption among the community, including among women of childbearing age. Objective: To determine the relationship between exposure to cigarettes and alcohol and the incidence of abortion among pregnant women in Village X. Methods: This study used a quantitative analytical design with a cross-sectional approach. A sample of 100 pregnant women and women who had experienced abortion in the past two years was selected using purposive sampling. Data were collected through questionnaires and structured interviews. Data analysis was performed using the Chi-Square test. Results: Of the 100 respondents, 35% experienced abortion. Passive smoking exposure was found in 60% of respondents, and light to moderate alcohol consumption in 25% of respondents. The Chi-Square test results showed a significant association between smoking exposure and abortion incidence (p = 0.002) and between alcohol consumption and abortion incidence (p = 0.018). Conclusion: There is a significant association between exposure to secondhand smoke and alcohol consumption with the occurrence of abortion in pregnant women in Village X. Educational efforts and reproductive health interventions are needed to reduce the risk of abortion due to exposure to harmful substances.